KAJIAN SISTEM AGRIBISNIS PAKCOY ORGANIK: KASUS PADA POKTAN SAUNG ORGANIK - Elly Rasmikayati; Mufti Helmi; Hesty Nurul Utami; Gunardi Judawinata; Bobby Rachmat Saefudin (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
The Saung Organic farmer group is a producer of organic vegetable products that has received an Organic Food Certificate from the Indonesian Organic Farming (Inofice) Certification in 2013 for the types of leafy vegetables including pakcoy. This study aims to examine the agribusiness system in organic pakcoy farming carried out by the Organic Saung Farmer Group. This study used a qualitative design with a case study method approach. The data analysis design used descriptive analysis. The results illustrate that in the upstream organic pakcoy subsystem, the procurement of production facilities includes pick-ups car, hoes, cored, sprayers, manure, organic liquid fertilizer, pakcoy gardena seeds, drilling wells to meet water availability, tricoderma, and packaging as well as tie rope. The production factor for organic pakcoy farming includes the area of land ownership in the group which is 0.5 hectares, does not use labor outside the farmer group members, and the amount of capital owned is Rp. 3,690,744. In the production subsystem, the organic pakcoy cultivation process is carried out with a cropping system system once every 15 days and planted in monoculture. Meanwhile, in the harvest and post-harvest subsystems, the harvest age for organic pakcoy plants is 30-33 days. In 1 year there are 12 planting and harvesting seasons. Organic pakcoy production reaches 1,434 kg / planting season. The post-harvest process includes washing, sorting, weighing and packaging. In marketing, consumers come directly to farmer groups to take orders.